Flexible Janus Functional Film for Adaptive Thermal Camouflage. Issue 3 (27th October 2021) - Liu, Yida; Zuo, Huaiyu; Xi, Wang; Hu, Run; Luo, Xiaobing
Abstract: With the increasing development of infrared (IR) detection technologies for both military and civil applications, IR anti‐detection technologies, also known as thermal camouflage technologies, have attracted great attention in recent years. Decreasing the surface emissivity may be effective for high‐temperature targets, but fails for adaptive thermal camouflage in dynamic scenes where the background temperature varies. In this work, we demonstrate a flexible Janus functional film (JFF) for adaptive thermal camouflage. The JFF consists of a low emissivity (low‐ε) layer and a high heat capacity (high‐ C ) layer. The low‐ε layer can effectively suppress the IR radiation of the objects, thus reducing the temperature of the objects in IR camera, while the high‐ C layer can make similar thermal response as the background. According to different environmental conditions, different surfaces of JFF can be selected as camouflage surface to achieve static or dynamic thermal camouflage effect. What's more, the substrate materials of JFF (i.e., high‐density polyethylene (HDPE), silica gel (SG)) enable the film with good flexibility and realize the encapsulation of the functional filler, thus improving its reliability of resisting water and oxygen. Such flexible JFF with high reliability, easy scalability, and low cost may hold great promise for broad applications in adaptive thermal camouflage. Abstract : A flexible Janus functional film (JFF) for adaptive thermal camouflage is demonstrated. The upper layer with low emissivity can effectively suppress the infrared radiation of the objects, while the lower layer with high thermal capacity can make similar thermal response as the background. According to different background scene, JFF can achieve static or dynamic thermal camouflage effect.